Misogyny and Sexism in Suffragette’s Main Character: A Marxist Feminist Analysis - Rosyalina Nur Aprilyani; Irma Rahmawati (Indo Publishing, 2025)
This research analyzes the portrayal of misogyny and sexism in the film Suffragette (2015), directed by Sarah Gavron, through the lens of Marxist feminist theory. The analysis uses Silvia Federici’s Marxist feminist theory, which sees that women’s oppression is rooted not only in patriarchy but also in capitalist systems that exploit women's unpaid labor and social roles. The study focuses on the main character, Maud Watts who is a working-class woman, whose experiences reflect gender and class oppression in early 20th-century Britain. Using a qualitative method, the researcher identified 24 key scenes in the film. Nine of them represent sexism and 15 represent misogyny. The findings show that sexism is normalized through unequal labor conditions, domestic expectations, and legal marginalization, while misogyny emerges as punishment when women resist these roles, often through violence and institutional control. Maud’s transformation from a passive worker to a politically active suffragette reveals the potential for collective resistance and highlights the importance of solidarity among women. The study concludes that Suffragette is not only a historical film but also as a powerful critique of ongoing gender and class inequalities.